Malabaricones from the fruit of Myristica cinnamomea King as potential agents against Acanthamoeba castellanii - Usman, Ahmed *; Sivasothy, Yasodha; Khan, Khalid Mohammed; Khan, Naveed Ahmed *; Siti Mariam, Abdul Wahab; Khalijah, Awang; Muhamad, Aqmal Othman; Ayaz, Anwar * (Elsevier, 2023)
Acanthamoeba castellanii is an opportunistic free-living amoeba (FLA) pathogen which can cause fatal central nervous system (CNS) infection, granulomatous amoebic encephalitis (GAE) and potentially blinding ocular infection, Acanthamoeba keratitis (AK). Acanthamoeba species remain a challenging protist to treat due to the unavailability of safe and effective therapeutic drugs and their ability to protect themselves in the cyst stage. Natural products and their secondary metabolites play a pivotal role in drug discovery against various pathogenic microorganisms. In the present study, the ethyl acetate extract of Myristica cinnamomea King fruit was evaluated against A. castellanii (ATCC 50492), showing an IC50 of 45.102 ± 4.62 µg/mL. Previously, the bio-guided fractionation of the extract resulted in the identification of three active compounds, namely Malabaricones (A-C). The isolated and thoroughly characterized acylphenols were evaluated for their anti-amoebic activity against A. castellanii for the first time. Among tested compounds, Malabaricone B (IC50 of 101.31 ± 17.41 µM) and Malabaricone C (IC50 of 49.95 ± 6.33 µM) showed potent anti-amoebic activity against A. castellanii trophozoites and reduced their viability up-to 75 and 80 %, respectively. Moreover, both extract and Malabaricones also significantly (p < 0.05) inhibit the encystation and excystation of A. castellanii, while showed minimal toxicity against human keratinocyte cells (HaCaT cells) at lower tested concentrations. Following that, the explanation of the possible mechanism of action of purified compounds were assessed by detection of the state of chromatin. Hoechst/PI 33342 double staining showed that necrotic cell death occurred in A. castellanii trophozoites after 8 h treatment of Malabaricones (A-C). These findings demonstrate that Malabaricones B and C could serve as promising therapeutic options against A. castellanii infections.